2009
DOI: 10.1001/jama.2009.1137
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Therapy Use for Prostate Cancer and Mortality in Men With Coronary Artery Disease–Induced Congestive Heart Failure or Myocardial Infarction

Abstract: Context Hormonal therapy (HT) when added to radiation therapy (RT) for treating unfavorable-risk prostate cancer leads to an increase in survival except possibly in men with moderate to severe comorbidity. However, it is unknown which comorbid conditions eliminate this survival benefit. Objective To assess whether neoadjuvant HT use affects the risk of all-cause mortality in men with prostate cancer and coronary artery disease (CAD)-induced congestive heart failure (CHF) or myocardial infarction (MI), CAD risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
147
4
9

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 267 publications
(166 citation statements)
references
References 51 publications
6
147
4
9
Order By: Relevance
“…8,9,16 These tests for interaction did not reach significance for either patient age (P = .82) or history of pre-RT CE (P = .40).…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…8,9,16 These tests for interaction did not reach significance for either patient age (P = .82) or history of pre-RT CE (P = .40).…”
Section: Resultsmentioning
confidence: 81%
“…5,6 Despite this evidence, controversy remains regarding the risks posed by ADT, with a recent pooled meta-analysis of randomized trials demonstrating no increased risk of cardiovascular mortality among patients treated with ADT in conjunction with RT, 7 and other studies suggesting that only subgroups of patients with pre-existing comorbidities may be at risk. 8,9 There remains even less consensus regarding the impact of ADT on non-fatal CEs, which can significantly impact patient quality of life but are often not captured in randomized trials and may not be reliably collected in population-based databases. Furthermore, while the cardiovascular effects of ADT have been studied in the setting of RT, it remains unclear whether these risks persist in the salvage setting after disease recurrence, in which ADT remains the standard first-line therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Of course, a major drawback to such aggressive treatment is increased toxicity, because the patient is exposed to potential complications from all 3 modalities. 28,29 However, our model did account for this increased toxicity.…”
Section: Discussionmentioning
confidence: 96%
“…21 If patients developed 1 of these conditions, then they were considered to have complications of hormone therapy, with the decreased utility secondary to hormones, for life. Whether hormone therapy is associated with an increased risk of cardiovascular mortality and/or all-cause mortality is highly controversial 28 ; nevertheless, we performed a sensitivity analysis on this question by assuming that hormone therapy is associated with an increase in all-cause mortality of 1.04 or 1.96 according to Nanda et al 29 Utilities Stewart et al elicited patient-perspective utilities for health states and toxicities associated with treatment using standard gambles with men aged 60 years who were treated for prostate cancer. 22 We used their derived utilities for all health outcomes, treatment preferences, and toxicities, as detailed in Table 1.…”
Section: Toxicitymentioning
confidence: 99%
“…Recently evaluation of patient outcomes for men on primary hormonal therapy for prostate cancer has demonstrated that these men are at signifi cantly increased risks for cardiac related deaths. This trend is especially apparent in patients with a previous history of cardiac disease [10]. Overall survival showed no signifi cant improvement with this therapy in several retrospective studies of large cohorts, and this has forced the oncologists to re-evaluate the role of ADT in localised cancer.…”
Section: Androgen Deprivation Therapymentioning
confidence: 99%